Otimização das etapas de produção de solução, contendo íons de ferro, via eletrólise e de regeneração para purificação de biogás - Tavares, Alexssander Juliano (2021)
The biogas produced by the anaerobic digestion of organic waste, depending on its intended use in boilers, heaters, and engines or as biofuel, needs to go through a purification process. Purification aims to reduce the concentrations of some compounds such as carbon dioxide (CO2) and hydrogen sulfide (H2S), which respectively reduce combustion power and cause serious corrosion problems. Among the operations most used to remove contaminants from biogas, absorption, adsorption, membrane filtration, biofiltration, microaeration and cooling can be mentioned. Among these, the most used is absorption with the use of a specific solution through simple solubilization or chemical reaction between the contaminant and a solute. One of the solutes used is iron (Fe), either in free form or chelated with some material. But the production of these chelated substances requires a specific process and makes the purification step more expensive. This work aims to present an efficient alternative for the purification of biogas through the production of a solution, containing iron ions, in the production plant, as well as the regeneration of this solution. The mechanism used to produce the solution was through the electrochemical corrosion of metallic iron plates subjected to different electrical currents, salt concentrations (NaCl) and time. To evaluate the efficiency of the prepared solutions, in the removal of H2S, and their regeneration, the Central Composite Rotational Design (CCRD) was used as a form of experimental planning. The iron concentrations of the solutions were determined immediately after their preparation and after the purification and regeneration tests. From the results, valid mathematical models were obtained to optimize the production and regeneration processes of the iron solution. It was found that there was a reduction in the concentration of Fe3+ ions during tests with biogas and it was possible to regenerate the solution, enabling its reuse.